Enhancing Stability and Emissions in Metal Halide Perovskite Nanocrystals Through Mn2⁺ Doping - Thi Thu Trinh Phan; Thi Thuy Kieu Nguyen; Trung Kien Mac; Minh Tuan Trinh (Nanomaterials)
Metal halide perovskite (MHP) nanocrystals (NCs) offer great potential for high-efficiency optoelectronic devices; however, they suffer from structural softness and chemical instability. Doping MHP NCs can overcome this issue. In this work, we synthesize Mn-doped methylammonium lead bromide (MAPbBr3) NCs using the ligand-assisted reprecipitation method and investigate their structural and optical stability. X-ray diffraction confirms Mn2⁺ substitution at Pb2⁺ sites and lattice contraction. Photoluminescence (PL) measurements show a blue shift, significant PL quantum yield enhancement, reaching 72% at 17% Mn2⁺ doping, and a 34% increase compared to undoped samples, attributed to effective defect passivation and reduced non-radiative recombination, supported by time-resolved PL data. Mn2⁺ doping also improves long-term stability under ambient conditions. Low-temperature PL reveals the crystal-phase transitions of perovskite NCs and Mn-doped NCs to be somewhat different than those of pure MAPbBr3. Mn2⁺ incorporation into perovskite promotes self-assembly into superlattices with larger crystal sizes, better structural order, and stronger inter-NC coupling. These results demonstrate that Mn2⁺ doping enhances both optical performance and structural robustness, advancing the potential of MAPbBr3 NCs for stable optoelectronic applications.